Neuromuscular Responses to 14 Weeks of Traditional and Daily Undulating Resistance Training - Ullrich, B.; Holzinger, S.; Soleimani, M.; Pelzer, T.; Stening, J.; Pfeiffer, M. (International Journal of Sports Medicine, 2015)
This study compared traditional (TP) and daily undulating (DUP) periodization on muscle strength, EMG-estimated neural drive and muscle architecture of the quadriceps femoris (QF). 10 non-athletic females (24.4±3.2 years) performed 14 weeks of isometric training for the QF exercising 1 leg using TP and the contralateral leg using DUP. Intensities varied from 60% to 80% of MVC and the intensity zones and training volume were equated for each leg. Knee extension MVC, maximal voluntary QF-EMG activity and vastus lateralis (VL) muscle architecture were measured in both legs before, after 6 weeks and after 14 weeks of training using dynamometry, surface EMG and ultrasonography. Isometric MVC and maximal QF-EMG remained unaltered after 6 weeks of training, but were significantly (P<0.05) enhanced after 14 weeks in both legs (MVC: TP 24%, DUP 23%; QF-EMG: TP 45%, DUP 46%). VL-architecture remained unchanged following 6 weeks of training, but VL-muscle thickness (TP 17%, DUP 16%) and fascicle length (TP 16%, DUP 17%) displayed significant (P<0.05) enlargements after 14 weeks in both legs. Importantly, these temporal neuromuscular alterations displayed no significant differences between the training legs. Therefore, periodization may not act as a key trigger for neuromuscular adaptations.
Keywords: muscle plasticity; quadriceps femoris; EMG; ultrasonography